Employability, managerialism, and performativity in higher education: a relational perspective - Kalfa, Senia; Taksa, Lucy (Higher Education, 2016)
This article combines Bourdieu’s concepts of field, habitus and cultural capital with Lyotard’s account of performativity to construct a three-tiered framework in order to explore how managerialism has affected the academic habitus. Specifically, this article examines the adoption of group assignments as a means of developing teamwork skills in one Australian case study organisation. On a macrolevel, by viewing the employability imperative as one manifestation of managerialism in the higher education field, we argue that managerialism has created a performative culture in the case study organisation evidenced by an increasing emphasis on performance indicators. On a mesolevel, by examining how academics use group assessments to respond to demands made by governments and employers for ‘employable graduates’, we highlight the continuity of academic habitus. Finally, on a microlevel by drawing on alumni reflections regarding their experiences of group assessments at university, we are able to shed some light on their evaluation of this pedagogical tool.